Penyelesaian Sengketa Penggantian Antar Waktu Anggota DPRD Provinsim Melalui Pengadilan Tata Usaha Negara - Pancasilawan, Mochammad Rizky Fauzi (jurnal.unprimdn.ac.id, 2024)
Interim replacement (PAW) is a mechanism in Indonesia's democratic system. Inter-Time Replacement (PAW) can be done to members of the legislature, one of which is a member of the DPRD. Interim Replacement (PAW) refers to the applicable laws and regulations. The existence of Interim Replacement (PAW) often causes legal disputes in the future, and someone feels mistreated by the Interim Replacement (PAW) and wants to file a lawsuit. As it is known against the existing Interim Replacement (PAW), the plaintiff makes a lawsuit through civil channels and the competence of the district court. In addition, the parties who feel aggrieved can also take the path to the State Administrative Court. This normative legal research uses a statutory approach and conceptual approach to answer the legal issues at hand.